Formulation of High Fiber Breakfast Food and Estimation of its Functional Qualities - Sharma, Sabitri; Paudyal, Bhupendra (Journal of Food Science and Technology Nepal, 2014)
This study aims to develop high fiber breakfast food rich in nutritional and functional components (β-glucan, antioxidants, and insoluble fiber) and identify the future possibilities of commercial product. Based on the 15 days survey carried out on Kathmandu, an optimum formulation (86% cereal, 5% nuts, 7% dried fruits and 2% pumpkin seed) of product was found at first 3 trails. Formulated sample was found to be superior in terms of nutritional qualities (protein %- 13.82±0.67, crude fiber %- 7.8±0.96, β-glucan%- 3.13±0.35, total polyphenol GAE- 458.33±10.4) and sensory qualities (color, flavor, size, shape, texture, overall acceptance) than market sample (Protein%- 12.39±1.54, crude fiber%- 5.18±0.9, β-glucan%- 1.18±0.07, total polyphenol GAE- 163.3±58.6). The product was further developed by varying processing methods (germinating, non-germinating wheat and instant (60°C) and gradual drying (50°C, 55°C, 60°C, 70°C)). Formulation having germinated wheat and instant dried (60°C) was found to be superior in terms of color, texture, avor and overall acceptance. The product was further subjected to chemical and functional analysis, cost analysis (Rs.42), microbiological analysis (TPC-1.8x103, Yeast count- 400cfu/g, Mold count- 300cfu/g), storage stability test (aw=0.113). Statistical analysis showed no significance difference among products of varying drying pattern but difference among germinated and non-germinated products. Consumer perceptibility test showed 64% of the consumer accepted muesli as the best product than commercial breakfast cereals. DOI: http://dx.doi.org/10.3126/jfstn.v7i0.10612 J. Food Sci. Technol. Nepal, Vol. 7 (76-80), 2012